Muscle adaptation to exercise: New Saltin's paradigms - Booth, F. W. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The title assigned for my lecture at the Saltin Symposium was "Muscle adaptation to exercise: new paradigms." The title's topic made me remember that some of Saltin's paradigms for his development of a novel exercise model were either originated by him or modified by him from existing information. Therefore, I deemed it would be instructive for future generations to consider one facet of his 54-year career - human exercise models. I arbitrarily selected to share five examples of new paradigm models initiated by Saltin. They are: bed rest; arms vs legs; one leg vs the other leg; myokine communication from skeletal muscle to other organs/tissues; and 42-day cross-country skiing expedition. I arbitrarily selected the above as examples of novel approaches that he used to the study humans during maximal endurance exercise. Noteworthy though is that Saltin's lifetime demeanor, itself, is a model for other scientists. In final analysis, the world is richer due to his passion to study humans to advance medical science by uncovering mechanisms as to how the human body is constructed to perform endurance types of exercise at maximal intensities and durations.